PELANGGARAN PRINSIP KERJA SAMA OLEH PEJABAT LEGISLATIF DAN TOKOH PARTAI TINGKAT KOTA DI SUMATRA BARAT DALAM MEDIA SOSIAL - Maharanni, Maharanni; Juita, Novia (Jurnal Bahasa dan Sastra, 2019)
The purpose of this study was to describe the forms of violations of the principle of cooperation by legislative officials and city level party leaders in West Sumatra on social media. This study used a qualitative-descriptive method. The data source in this study is in the form of speech in the Facebook status of officials and party leaders. The object of this research is the speech on Facebook of legislative and party leaders. Data collection was carried out by (1) printing screenings on Facebook of city-level legislative and party leaders in West Sumatra; (2) transcribing writings on facebook city level legislative and party figure officials in West Sumatra; (3) pay close attention to the writings on Facebook of city-level legislative and party figure officials in West Sumatra which are included in the section on language performance and politeness of communication; and (4) determine data included in the language performance section and politeness of written communication. Analyzing data is done with the aim of grouping data, analyzing data, and determining conclusions.Keywords: performance, facebook, linguistic, communication